Intracranial atherosclerotic stenosis in Asia: a systematic scoping and rapid review of prevalence, frequency in ischaemic stroke and risk factors - Robert N Gan; Johnny K Lokin; Romulo U Esagunde; Jose C Navarro; Bonifacio Pedregosa; Monique Therese S Punsalan; Gabriel Alejandro B Baroque; Maria Socorro F Sarfati; Maria Teresa A Cañete; Anna Marie Sage-Nolido; John Harold B Hiyadan; Laurence Kristoffer J Batino; et al. (BMJ Neurology Open)
Background The burden and profile of intracranial atherosclerotic stenosis (ICAS) among Asians remain incompletely understood. We aimed to describe and review the current body of literature on the prevalence of ICAS, its frequency among patients with ischaemic stroke and its associated risk factors across different Asian populations, taking into account the diagnostic modalities and criteria used to identify ICAS in these studies.Methods We performed a systematic scoping and rapid review of published studies reporting on the prevalence, frequency in ischaemic stroke and risk factors associated with ICAS in Asian populations.Results Of the 1272 identified citations, 142 were included in the final review: 54 studies reported on prevalence, 56 on frequency in ischaemic stroke and 120 on risk factors. Most studies were conducted in China, Hong Kong, Korea and Japan. Reported ICAS prevalence varied widely, from 3% to 89.4% (median 13%), while frequency in ischaemic stroke ranged from 7.9% to 82.4% (median 41.65%). Magnetic resonance and transcranial ultrasonography were the most frequently used diagnostic modalities, with most studies applying a ≥50% stenosis threshold. Associations between ICAS and traditional (eg, age, hypertension, diabetes, dyslipidaemia, smoking and prior stroke), genetic and other emerging risk factors were reported, although the strength and consistency of associations varied.Conclusion Our review supports the prevailing understanding of a relatively higher burden of ICAS among Asians, while also underscoring the substantial heterogeneity in reported prevalence and frequency in ischaemic stroke of ICAS across Asian populations. Variability in diagnostic modalities and criteria used to identify ICAS likely influenced these rates. While a range of risk factors has been identified, the strength and consistency of associations vary. The concentration of studies in East Asia underscores the need for further research, particularly in under-represented countries. The standardisation of diagnostic criteria and imaging protocols for ICAS is needed.Registration https://doi.org/10.17605/OSF.IO/PKVJ3